2020
DOI: 10.1371/journal.pone.0238587
|View full text |Cite
|
Sign up to set email alerts
|

Score performance of SAPS 2 and SAPS 3 in combination with biomarkers IL-6, PCT or CRP

Abstract: We aimed to evaluate the effects of combining the Simplified-Acute-Physiology-Score (SAPS) 2 or the SAPS 3 with Interleukin-6 (IL-6) or Procalcitonin (PCT) or C-Reactive Protein (CRP) concentrations for predicting in-hospital mortality. Material and methods This retrospective study was conducted in an interdisciplinary 22-bed intensive care unit (ICU) at a German university hospital. Within an 18-month period, SAPS 2 and SAPS 3 were calculated for 514 critically ill patients that were admitted to the internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
2
0
1
Order By: Relevance
“…Combining SAPS-3 with other biomarkers, such as IL-6 and lactate, as demonstrated previously [36,37], could significantly enhance the predictive accuracy of patient outcomes. In our study, first lactate proved to be the most effective predictor of outcomes when combined with SAPS-3, with an AUC of 80.6%.…”
Section: Discussionmentioning
confidence: 78%
“…Combining SAPS-3 with other biomarkers, such as IL-6 and lactate, as demonstrated previously [36,37], could significantly enhance the predictive accuracy of patient outcomes. In our study, first lactate proved to be the most effective predictor of outcomes when combined with SAPS-3, with an AUC of 80.6%.…”
Section: Discussionmentioning
confidence: 78%
“…In a retrospective cohort study, Jahn et al showed that patients with higher SAPS 2 and 3 values at admission were more prone to death. (35) In addition to greater severity, H1 patients had a higher workload. The association between higher admission severity and higher nursing workload has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study, Jahn et al showed that patients with higher SAPS 2 and 3 values at admission were more prone to death. ( 35 )…”
Section: Discussionmentioning
confidence: 99%
“…A major concern about some popular disease severity assessment scores is the limited consideration of inflammatory processes and/or immune dysfunction that is particularly important in cirrhotic patients [42, 43]. Therefore, new markers that register oxidative stress or cell death might likely enhance score performance [44, 45].…”
Section: Discussionmentioning
confidence: 99%